The Correlation between Subjective Well-Being and Job Satisfaction among PPPK Teachers - Valensia, Karen Joe; Wibowo, Doddy Hendro (Universitas Nusa Cendana, 2023)
This study explored the relationship between subjective happiness and job satisfaction among PPPK teachers. This research involved 77 PPPK teachers from junior and senior high schools in Pekalongan. A nonprobability sampling method employing saturation sampling was utilized in this study. The Subjective Well-being Scale (25 items, α=0.902) was used to measure subjective happiness, while the Job Satisfaction Scale (23 items, α=0.921) was used to measure job satisfaction. Data analysis using Pearson's product-moment correlation revealed a significant positive correlation between subjective happiness and job satisfaction among PPPK teachers (r_xy=0.596; p=0.000, p<0.05). These findings indicate that higher levels of subjective happiness are associated with higher job satisfaction among PPPK teachers. This discovery holds important implications for PPPK teachers in enhancing their job satisfaction and effectiveness in fulfilling their educational roles.